Influence of Recycled Concrete Aggregate and Crushed Clay Brick on Mechanical Properties of Concrete - Osiregbeme Momoh, Garuba; Sundaram, Hemavathi; Shanmugam, Thiru; Deepak, Tirumishi Jada (Academic Hosting & Event Management Solutions, 2015)
Concrete is regarded as the most used construction material and natural aggregates used in concrete must be preserved by any acceptable means. This paper presents the results; compressive strength and tensile strength, of using Recycled Concrete Aggregate (RCA) and Crushed Clay Brick (CCB) as partial replacements for coarse and fine aggregates respectively in concrete. Three factors: RCA, CCB and CD were considered and combined at different levels of replacement in the determination of the compressive and tensile strength of concrete. The Response Surface Methodology (RSM) was used to determine the combination of these factors. RCA was used at 30%, 22.5% and 15% representing the high, middle and low replacement levels. Similarly, CCB was replaced at 20%, 15% and 10% which represents the high, middle, and low level respectively. CD was set to 28, 18 and 7 days representing the high, middle and low level. 20 combination set was generated using the RSM. It was found that RCA and CCB included concrete gains compressive strength faster within the first 7 days than the Normal Aggregate Concrete (NAC) but may not gain much more strength afterwards.